2013
DOI: 10.1021/nl403669a
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reversible Open Framework Nanoscale Electrodes for Divalent Ion Batteries

Abstract: The reversible insertion of monovalent ions such as lithium into electrode materials has enabled the development of rechargeable batteries with high energy density. Reversible insertion of divalent ions such as magnesium would allow the creation of new battery chemistries that are potentially safer and cheaper than lithium-based batteries. Here we report that nanomaterials in the Prussian Blue family of open framework materials, such as nickel hexacyanoferrate, allow for the reversible insertion of aqueous alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
402
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 463 publications
(418 citation statements)
references
References 48 publications
12
402
1
3
Order By: Relevance
“…11,12 In such a case, an active material with large channels that allow the passage of hydrated polyvalent cations is necessary. Wang et al 13,14 observed that various polyvalent cations could rapidly diffuse into Prussian Blue analogue (PBA) electrodes, which contain large open interstitial sites (4.6 ¡ in diameter) and ©100ª channels (3.2 ¡ in diameter) in polyvalent cation-based aqueous electrolytes. However, the low charge/discharge capacities and capacity reduction during the initial cycles must be improved.…”
Section: +mentioning
confidence: 99%
“…11,12 In such a case, an active material with large channels that allow the passage of hydrated polyvalent cations is necessary. Wang et al 13,14 observed that various polyvalent cations could rapidly diffuse into Prussian Blue analogue (PBA) electrodes, which contain large open interstitial sites (4.6 ¡ in diameter) and ©100ª channels (3.2 ¡ in diameter) in polyvalent cation-based aqueous electrolytes. However, the low charge/discharge capacities and capacity reduction during the initial cycles must be improved.…”
Section: +mentioning
confidence: 99%
“…1a). Each unit cell consists of eight subunit cells and therefore contains eight interstitial sites that can host various ions, such as Li þ , Na þ , K þ , NH 4 þ , Rb þ , alkaline earth divalent ions and zeolitic water 16,17 . The open-framework nature of the cubic structure, which contains open o1004 channels (3.2 Å in diameter) and interstitial sites (4.6 Å in diameter) in the case of Prussian Blue 18 , enables rapid solid-state diffusion of a wide variety of ions.…”
mentioning
confidence: 99%
“…The synthesis process follows the method reported by Wang et al [15]. However, as we wanted to further explore the ZnHCF synthesis method to optimize the cathode material for ARZIBs, in this study, three materials were synthesized by using aqueous solutions with three different concentrations of Zn(NO 3 ) 2 (Alfa Aesar, 99%).…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics have been demonstrated by the wide application of ARZIBs to devices used in the body, such as hearing aids. In addition, ARZIBs are expected to have relatively high capacities because of the high theoretical value for zinc metal anodes (820 mAh g -1 ), as well as low costs owing to their relatively simple manufacturing processes and the abundance of zinc resources [13][14][15]. In recent years, various materials, such as manganese dioxide and Prussian blue analogues (PBA), have been reported as cathode materials for ARZIBs [16,17].…”
Section: Introductionmentioning
confidence: 99%